Socioeconomic disparities in Malaysia during the Covid-19 pandemic: an exploratory study - Zuraidah Mohamed Isa,; Norhidayah Ali,; Dahlia Ibrahim,; Azyyati Anuar,; Suhaida Abu Bakar,; Nor Salwati Othman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
COVID-19 has shocked the world with an overwhelming number of people infected by it. Without a doubt, Malaysia is no exception to this pandemic chaos. Within weeks, Malaysia made the top of the list in Southeast Asia with the most confirmed COVID-19 cases. As a consequence, the Prime Minister had no choice but to call for a sudden Movement Controlled Order (MCO) that affected most of the workers and businesses. Therefore, this study investigated the effect of the COVID-19 pandemic on Malaysia’s socioeconomic condition. We surveyed the entire Malaysian population from the age of 18 to 65 years and above, with a 516 minimum sample size. A convenience sampling technique is utilised where the respondents receive a URL link through WhatsApp group and email. According to Krejcie and Morgan, 384 was the minimum sample size for this study. This study applied Raosoft software to determine the sample size with a 95% confidence level. From the software, the sample size is estimated at 385. The result of the study proved that the COVID-19 pandemic does influence the socioeconomic status of society, as there is a significant association between the COVID-19 pandemic and socioeconomic factors. To conclude, future researchers can further explore the impact of the COVID-19 pandemic on the socioeconomic status of a population. Researchers can include other relevant socioeconomic factors with a more scattered demographic profile of respondents to achieve a more robust and unbiased result.